Agriculture, trade and the environment : the pig sector - Organisation for Economic Co-operation and Development (OECD, 2003)
Summary and conclusions (s. 11-22).
Keywords: maatalouden tukeminen : OECD-maat; karjatalous : OECD-maat; karjatalous : ympäristövaikutukset